Economic policy uncertainty and return on financial assets: the G7 case - Carvalho, Teresa Lopes de (2018)
This dissertation aims at understanding the impact of economic policy uncertainty on the stock and bond market returns of the group of seven. We test the hypothesis that higher uncertainty levels cause decreases on these financial assets returns. We analyse the impact that the economic policy uncertainty index and previous returns have on current returns and if an increase of economic policy uncertainty lead to an increase of conditional volatility. This research relies on the EPU Index, developed by Baker et al. (2016), and employs daily data averaged into monthly time series for G7 stock and bond markets, covering the period from January 2000 to December 2016. Concerning the stock market, we find evidence of a significant impact of EPU on current returns for most of the countries. Canada and Italy are the exceptions. Concerning conditional volatility, we report that the EPU has impact on United States (U.S.), United Kingdom (U.K.), Canada, Germany and Japan. EPU does not show significant results to France and Italy. In the bond market and in contrast with previous returns, EPU does not have a great impact on the current returns for most of the countries. In what concerns conditional volatility, the previous returns have no influence for the entire sample and EPU presents significant results for U.S., Canada, Germany, Italy and Japan.